Guidelines for Audio-Visual Services in Academic Libraries - Association of Coll. and Research Libraries, Chicago, IL.; Association of Coll. and Research Libraries, Chicago, IL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
The purpose of these guidelines, prepared by the Audio-Visual Committee of the Association of College and Research Libraries, is to supply basic assistance to those academic libraries that will assume all or a major portion of an audio-visual program. They attempt to assist librarians to recognize and develop their audio-visual responsibilities and to incorporate the newer media within the traditional concepts of library service, and should not be considered an accrediting measurement. They contain no quantitative standards since these will vary with each institution depending on the extent of that institution's involvement in an audio-visual program. Topics covered in the guidelines include: planning, types of materials, equipment, budget, personnel, facilities, selection, acquisition and cataloging, collection organization and maintenance, and service. A bibliography of 115 items is appended. (Author/JB)
Availability: American Library Association, 50 East Huron St., Chicago, Illinois 60611 ($1.50).
Educational level discussed: Two Year Colleges.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Libraries; Audiovisual Centers; Bibliographies; Cataloging; Library Acquisition; Library Facilities; Library Material Selection; Library Services; Two Year Colleges; Audiovisual Aids; Audiovisual Instruction; College Libraries; Guidelines